Effects of nano-silver pulsing, calcium sulfate and gibberellin on an antioxidant molecule and vase life of cut gerbera flowers - Shafiee-Masouleh, Seyedeh-Somaye (Advances in Horticultural Science, 2018)
Abstract: The aim of this study was to evaluate interactions between NS coupled with CS and GA on flavonoid, cell membrane behavior and extending the vase life of cut gerbera. Pulse treatments of flowers in NS at concentrations 0 (DI), 3 or 9 mg/l for 24 h. Then, flowers were treated with preservative solutions containing calcium sulfate (0, 10 or 20 mM) and GA4+7 (0 or 20 mg/l), plus 1.5% sucrose in all preservative solutions. Pulse treatments with 3 or 9 mg NS/l and holding in solution containing 20 mM CS compared to the control treatment (holding in the solution of sucrose following pulse treatment in DI) significantly extended vase life by 8 days. According to the antioxidant role of flavonoids, and lower amounts of flavonoid in the flowers that pre-treated with NS, therefore, it may be said that NS prevented from microbial attack.